Pengaruh Relaksasi Aromaterapi Jasmine terhadap Kualitas Tidur pada Lansia di Karang Werdha - Mahda Febriyanti Eka Pertiwi Putri; Murtaqib Murtaqib; mulia hakam (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
During the quality of sleep the elderly is good, some changes that will occur to the elderly arenormal as well, but if not, it will cause health problems. This research aims to analyze theeffect of jasmine aromatherapy relaxation on sleeping quality to the elderly at elderlyassociation in Jenggawah Jember. This research used quasy experimental design methodwith pre-post test and control group design. Sleeping quality was measured using a PSQIquestionnaire and interventions which were given for 28 days. The result of dependent t testshowed no significant difference on the average score of control group (p value = 1,000).While in the intervention group there was a decrease in the mean score of PSQI after beinggiven jasmine aromatherapy relaxation, so that there was a significant difference in sleepingquality of the intervention group (p value = 0,001). Independent t tests showed significantdifferences between the control group and the intervention group after jasmine aromatherapyrelaxation (p value = 0,001). Overall, jasmine aromatherapy relaxation can improve sleepingquality in the elderly, so that jasmine aromatherapy relaxation may be used as an alternativenon-pharmacological treatment which has no adverse side effects compared to the use oflong-term sleeping pills that would give negative side effects to its users. Keywords: aromatherapy, sleeping quality, elderly.